FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KEPATUHANAN MASYARAKAT TERHADAP PENERAPAN PROTOKOL KESEHATAN COVID- - Tedi Ardiansyah; Nia Triswanti; Sandhy Arya Pratama; Sri Maria Puji Lestari (Medula, 2023)
ovid-19 is an infectious disease caused by a type of coronavirus, according to data from the Lampung Provincial Health Office in December 2021 there were 49,715 positive confirmed cases and 3,825 deaths, the work area of ​​the Segala Mider Health Center is the area with the 5th most Covid-19 cases in the Bandar Lampung with a total of 642 cases, the purpose of this study was to determine the factors that influence the level of community compliance with the Covid-19 health protocol in the work area of ​​the All Mider Public Health Center in 2022. This research is descriptive analytic using survey method with short Cross-sectional analysis The sample in this study was taken in the work area of ​​the Segala Mider Health Center, Lampung Province in 2022 as many as 100 people were selected by the Accidental Sampling technique. Data were taken using a questionnaire and statistically tested with univariate and bivariate Pearson Chi-Square using SPSS. Pearson Chi-Square test found a relationship between knowledge (p-value= 0.000), attitudes (p-value= 0.000), motivation (p-value=0.000), age (p-value=0.000) and education (p-value= 0.000) with the level of compliance and there is no relationship between gender (p-value= 0.199) with the level of compliance in the implementation of the Covid-19 health protocol in the work area of ​​the Segala Mider Public Health Center in 2022. There is a relationship There is a significant relationship between knowledge, motivation, age and education with the level of community compliance with the Covid-19 health protocol in the work area of ​​the Segala Mider Public Health Center in 2022.